Dual TTK/PLK1 inhibition has potent anticancer activity in TNBC as monotherapy and in combination - Zanini, Elisa; Forster-Gross, Nicole; Bachmann, Felix; Brüngger, Adrian; McSheehy, Paul; Litherland, Karine; Burger, Karin; Groner, Anna C.; Roceri, Mila; Bury, Luc; Stieger, Martin; Willemsen-Seegers, Nicole; et al. (Frontiers in Oncology, 2024)
Threonine Tyrosine Kinase (TTK) and Polo-Like Kinase 1 (PLK1) are common essential kinases that collaborate in activating the spindle assembly checkpoint (SAC) at the kinetochore ensuring appropriate chromosome alignment/segregation prior to mitotic exit. BAL0891 is a first in class, dual TTK/PLK1 inhibitor with a prolonged effect on TTK and a transient activity on PLK1. This unique profile potentiates SAC disruption, forcing tumor cells to aberrantly exit mitosis, with faster kinetics than observed with a TTK-specific inhibitor. With broad anti-proliferative activity across solid tumor cell lines in vitro, intermittent intravenous single-agent treatment of the MDA-MB-231 mouse model of human triple negative breast cancer (TNBC) induces profound tumor regressions associated with prolonged TTK and transient PLK1 in-tumor target occupancy. Furthermore, differential tumor responses across a panel of thirteen TNBC patient-derived xenograft models indicated profound anticancer activity in a sub-set. Using a flexible dosing approach, pathologically confirmed cures were observed in combination with paclitaxel, whereas synergy with carboplatin was schedule dependent. Hence, dual TTK/PLK1 inhibition represents a novel approach for the treatment of human cancer, including TNBC patients.